2013
DOI: 10.3844/jcssp.2013.708.715
|View full text |Cite
|
Sign up to set email alerts
|

Sound and Digital Class Room: Smart Way to Have a Language Laboratory

Abstract: Development of information technology encourages educational institution to run the multimedia system interactively and easily. Multimedia technology that has video and audio streaming element takes an important role in interactive teaching activities between teachers and students. Streaming or transmission of video and audio has bandwidth, delay and loss packet. The objective is to design and develop an interactive multimedia system for language classroom to facilitate learning activities. The system is conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Just like the traditional physical language lab was visited as part of the learning experience, participants accessed this language laboratory through virtual means apart from class. It was clear that this experience modernized the laboratory experience as it included current tools (Lokmacioğlu et al, 2015) and activities that promoted learning (Yulianto et al, 2013). Via the synchronous tool Zoom and asynchronous tools of Edmodo and Wikispaces, participants collaborated through CALL resources (Karpova et al, 2009;Lin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just like the traditional physical language lab was visited as part of the learning experience, participants accessed this language laboratory through virtual means apart from class. It was clear that this experience modernized the laboratory experience as it included current tools (Lokmacioğlu et al, 2015) and activities that promoted learning (Yulianto et al, 2013). Via the synchronous tool Zoom and asynchronous tools of Edmodo and Wikispaces, participants collaborated through CALL resources (Karpova et al, 2009;Lin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the affordances of the physical language laboratory realized during its peak and the present-day value seen in using synchronous and asynchronous technological tools in the classroom, this study will create a personalized online language laboratories with these synchronous and asynchronous tools. Although current research has shown that the integration of a physical language laboratory is beneficial to L2 learners (Mohammed, 2017;Navas Brenes, 2006) and that tools should include modern (Lokmacioğlu et al, 2015) and interactive (Yulianto et al, 2013) tools, this study is the first to propose the creation of a completely online language laboratory. Therefore, this study will answer the following research questions (RQs): RQ1: What are the affordances for L2 learners of an online language laboratory created from synchronous and asynchronous tech tools?…”
Section: Research Questionsmentioning
confidence: 98%
“…REST also now emerging as alternative to SOAP-based web service with better performance (Yulianto et al, 2013). This publication will attempt to explore a possibility of creating new lifestyle of learning that aim to provide rich feature mobile device learning lab, fully customized learning style and lifelong mobile language learning.…”
Section: Introductionmentioning
confidence: 99%
“…Lecturers can write or draw anything on the board digitally and able to capture the writing on the board and then save or share it to students for reviewing. Not only cover the drawbacks on previous whiteboard version, the interactive whiteboard are also expected can increase student interest in teaching learning activities in classroom (Yulianto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%